Antioxidant and Antimicrobial Activities of Thai Edible Plant Extracts Prepared Using Different Extraction Techniques - Pimmada Junsathian; Soichiro Nakamura; Shigeru Katayama; Saroat Rawdkuen (Molecules, 2022)
This study investigated the antioxidant and antimicrobial activities of six Thai edible plant leaf extracts, including Cashew (CN), Chamuang (CM), Monpu (MP), Thurianthet (TT), Kradon (KD) and Pakliang (PL), extracted using ethanol extraction (EE), microwave-assisted extraction (MAE), and ultrasonic-assisted extraction (UAE). The leaf extracts were characterized for percentage yield, total phenolic content (TPC), total flavonoid content (TFC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) and-ferric reducing antioxidant power (FRAP) activity, and antimicrobial activity against spoilage. MAE produced the highest percentage yields, among which MAE-extracted MP exhibited the highest yield. Furthermore, the highest TPC and TFC were obtained for MAE, with MAE-extracted KD and CN showing the highest TPC and TFC, respectively, among the samples. The highest DPPH and FRAP values were seen in MAE-processed CN, KD, and MP extracts. The inhibition zone of pathogenic bacteria, minimum inhibitory concentration, and minimum bacterial concentration were determined in all samples except TT. These findings indicate that, compared to EE and UAE, MAE improved the antioxidant and antimicrobial efficacy of the leaf extracts. The aforementioned extracts could be employed as natural food additives to prevent chemical and microbial spoilage of foods.